Cold War Mary : Ideologies, Politics, and Marian Devotional Culture - Margry, P. J. (Peter Jan) (Book collections on Project MUSE., 2020)
One hardly known but fascinating aspect of the Cold War was the use of the holy Virgin Mary as a warrior against atheist ideologies. After the Second World War, there was a remarkable rise in the West of religiously inflected rhetoric against what was characterised as "godless communism". The leaders of the Roman Catholic Church not only urged their followers to resist socialism, but along with many prominent Catholic laity and activist movements they marshaled the support of Catholics into a spiritual holy war. In this book, experts address a variety of grassroots and Church initiatives related to Marian politics, the hausse of Marian apparitions during the Cold War period, and the present-day revival of Marian devotional culture. By identifying and analysing the militant side of Mary in the Cold War context on a global scale for the first time, this book will draw the attention of readers interested in religious history, the history of the Cold War, and twentieth-centuryinternational history.